Medical Expenditures and Earnings Losses Among US Adults With Arthritis in 2013 - Murphy, Louise B.; Cisternas, Miriam G.; Pasta, David J.; Helmick, Charles G.; Yelin, Edward H. (Arthritis care & research (2010), 2018)
Objective We estimated the economic impact of arthritis using 2013 US Medical Expenditure Panel Survey (MEPS) data. Methods We calculated arthritis‐attributable and all‐cause medical expenditures for adults age ≥18 years and arthritis‐attributable earnings losses among those ages 18–64 years who had ever worked. We calculated arthritis‐attributable costs using multistage regression‐based methods, and conducted sensitivity analyses to estimate costs for 2 other arthritis definitions in MEPS. Results In 2013, estimated total national arthritis‐attributable medical expenditures were $139.8 billion (range $135.9–$157.5 billion). Across expenditure categories, ambulatory care expenditures accounted for nearly half of arthritis‐attributable expenditures. All‐cause expenditures among adults with arthritis represented 50% of the $1.2 trillion national medical expenditures among all US adults in MEPS. Estimated total national arthritis‐attributable earning losses were $163.7 billion (range $163.7–$170.0 billion). The percentage with arthritis who worked in the past year was 7.2 percentage points lower than those without arthritis (76.8% [95% confidence interval (95% CI)] 75.0–78.6 and 84.0% [95% CI 82.5–85.5], respectively, adjusted for sociodemographics and chronic conditions). Total arthritis‐attributable medical expenditures and earnings losses were $303.5 billion (range $303.5–$326.9 billion). Conclusion Total national arthritis‐attributable medical care expenditures and earnings losses among adults with arthritis were $303.5 billion in 2013. High arthritis‐attributable medical expenditures might be reduced by greater efforts to reduce pain and improve function. The high earnings losses were largely attributable to the substantially lower prevalence of working among those with arthritis compared to those without, signaling the need for interventions that keep people with arthritis in the workforce.